2019
DOI: 10.1080/23802359.2019.1674726
|View full text |Cite
|
Sign up to set email alerts
|

The first complete mitochondrial genome of Murex from Murex trapa (Neogastropoda: Muricidae)

Abstract: The rare-spined murex (Murex trapa) is an ecologically and economically important species of Muricidae, which comprises a highly diverse group of predatory marine snails. However, the taxonomic classification and phylogenetic studies have so far been limited. In this study, we report the first complete mitochondrial genome of Murex from M. trapa. The mitogenome has 15,408 bp (66.3% A þ T content) and made up of total of 37 genes (13 protein-coding, 22 transfer RNAs, and 2 ribosomal RNAs), and a control region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Among these genes, 13 PCGs, 14 tRNAs ( trnD , trnV , trnL1 , trnL2 , trnP , trnS1 , trnH , trnF , trnK , trnA , trnR , trnN , trnI and trnS2 ), and 2 rRNAs ( rrnS and rrnL ) were encoded on the major strand, whereas the other eight tRNAs ( trnM , trnY , trnC , trnW , trnQ , trnG , trnE and trnT ) were encoded on the minor strand. The gene order of the 11 muricid mt genomes (Figure 1) was identical to that of other reported neogastropod mt genomes (Brauer et al, 2012; Cunha et al, 2009; Yang et al, 2020; Zhong et al, 2019).…”
Section: Resultssupporting
confidence: 79%
“…Among these genes, 13 PCGs, 14 tRNAs ( trnD , trnV , trnL1 , trnL2 , trnP , trnS1 , trnH , trnF , trnK , trnA , trnR , trnN , trnI and trnS2 ), and 2 rRNAs ( rrnS and rrnL ) were encoded on the major strand, whereas the other eight tRNAs ( trnM , trnY , trnC , trnW , trnQ , trnG , trnE and trnT ) were encoded on the minor strand. The gene order of the 11 muricid mt genomes (Figure 1) was identical to that of other reported neogastropod mt genomes (Brauer et al, 2012; Cunha et al, 2009; Yang et al, 2020; Zhong et al, 2019).…”
Section: Resultssupporting
confidence: 79%
“…The complete mitogenome of C. asianus was 15,361 bp in length (GenBank accession number: MN793976), and containing the typical set of 13 protein-coding, 22 tRNA and 2 rRNA genes, and a putative control region. The overall base composition of the mitogenome was estimated to be A 27.9%, T 37.6%, C 16.0% and G 18.5%, with a high A þ T content of 65.2%, which is similar, but slightly lower than Murex trapa (66.3%) (Zhong et al 2019b). The mitogenomic phylogenetic analyses showed that C. asianus and C. torrefactus clustered in a single clade then clustered with M. trapa with high bootstrap value (Figure 1), which is consistent with the phylogenetic analyses of Muricidae using the entire 18S rRNA, histone H3, and three partial mitochondrial genes (Zou et al 2011).…”
mentioning
confidence: 96%
“…However, the phylogeny and classification of Muricidae are still debated due to the morphological convergence and plasticity (Barco et al 2010;Zou et al 2011). The complete mitochondrial genome is an enhance resolution to recover phylogenetic relationships in Muricidae, but mitogenome information in Muricidae is still inadequate (Zhong et al 2019b). Here, we report the complete mitochondrial genome sequence of C. asianus, which will provide a better insight into phylogenetic assessment in Muricidae.…”
mentioning
confidence: 97%
“…The order Neogastropoda is a highly diversified group of predatory marine gastropods, which comprise more than 16,000 described species and has adapted to almost every marine environment including the abyssal zone of the oceans (Zou et al 2011). Neogastropoda contains the most geographically widespread and ecologically diverse families including Muricidae (Zhong et al 2019a), Nassariidae, Buccinidae (Zhong et al 2019b) and Volutidae. Many species of Volutidae including Melo melo are economically important as luxury seafood and valuable ingredients of traditional medicines (Kanagasabapathy et al 2011).…”
mentioning
confidence: 99%
“…Neogastropoda contains the most geographically widespread and ecologically diverse families including Muricidae (Zhong et al. 2019a ), Nassariidae, Buccinidae (Zhong et al. 2019b ) and Volutidae.…”
mentioning
confidence: 99%